Estimating the number of coding mutations in genotypic- and phenotypic-driven N-ethyl-N-nitrosourea (ENU) screens. - Keays, D; Clark, T; Flint, J (2006)
N-ethyl-N-nitrosourea (ENU) is a widely used mutagen in genotypic and phenotypic screens aimed at elucidating gene function. The high rate at which ENU induces point mutations raises the possibility that an observed phenotype may be to the result of another unidentified linked mutation. This article presents methods for estimating the probability of additional linked coding mutations (1) in a given region of DNA using both Poisson and Bayesian models and in (2) an F(1) animal exposed to ENU that has undergone b number of backcrosses. Applying these methods to the mouse data set of Quwailid et al., we estimate that the probability that a confounding mutation is linked to a cloned mutation when the candidate region is 5 Mb is very slim (p < 0.002). Where mutants are identified by genotypic methods, we show that backcrossing in the absence of marker-assisted selection is an inefficient means of eliminating linked confounding mutations.